Cormier, Leonard. Tune on the fiddle. - Bennett, Margaret
An audio clip of Leonard playing the fiddle. King George (strathspey) and Muileann Dubh (reel). Stathspeys (not generally encountered in the rest of Newfoundland) characterize the instrumental music of Codroy Valley, and are often followed by a reel. They are generally played for step-dancing.